Learning styles as predictors of grades in geometry - Baña, Edward E (Iloilo City University of the Philippines Visayas, 2009)
This quasi-experimental study was conducted in order to understand the relationship between the learning styles and grades in Geometry of 150 year students of Antique Vocational School during the school year 2008-2009. It sought to determine the regression model that can be used to predict the grades of the students based on their learning styles. The learning styles were determined using the Learning Style assessment which was adapted from E-world services, Inc. Handbook, cited by Bogod (2006). Using this this instrument, the students are classified as visual, auditory, or tactile learners. Dominnt learning style of each student was identified using ratio and percentage. The grades in Geometry, on the othr hand, are the grades of students for the third grading period which starts in October, 2008 and ends in January, 2009. The computed Pearson correlation coefficient shows that there is a significant relationship between the dominant learning styles and Grades in Geometry of the 150 third year students. Only two learning styles-auditory and visual- were identified as significant predictors of students' grades in Geometry. The model shows that there is direct relationship between the auditory learning style and grades in Geometry while tactile learning style and grades have an indirect relationship.
Special Problem (M.Ed.-Mathematics) -- Iloilo City : U.P. Visayas, 2009.